2012
DOI: 10.2903/sp.efsa.2012.en-357
|View full text |Cite
|
Sign up to set email alerts
|

Literature review on the sensitivity and exposure of marine and estuarine organisms to pesticides in comparison to corresponding fresh water species

Abstract: To compare the sensitivity and exposure of marine and estuarine species (further noted as saltwater) to pesticides to those of freshwater species we searched the peer reviewed literature. Relevant literature references were assembled in two EndNote libraries, one on saltwater species, and one on freshwater species, comprising a total of 3627 references. Based on an extensive toxicity database and the EndNote libraries we developed Species Sensitivity Distributions (SSDs) to assess differences in sensitivity. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 111 publications
2
9
2
Order By: Relevance
“…The results of the present analysis are consistent with earlier analyses of freshwater and saltwater sensitivity to chemicals [2][3][4][5][6][7]. They show that saltwater fish species are generally no more sensitive than freshwater species and that when they are more sensitive to a plant protection or biocidal product active substance, the difference in sensitivity is usually less than a factor of 10.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present analysis are consistent with earlier analyses of freshwater and saltwater sensitivity to chemicals [2][3][4][5][6][7]. They show that saltwater fish species are generally no more sensitive than freshwater species and that when they are more sensitive to a plant protection or biocidal product active substance, the difference in sensitivity is usually less than a factor of 10.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier reports suggested that freshwater fish test results are broadly predictive (within a factor of approximately 10) of effects on saltwater fish , based mainly on short‐term lethal data rather than on longer‐term studies. For example, Wheeler et al , building on work by Leung et al , compared species sensitivity distributions (SSDs) for freshwater and saltwater median lethal concentration (LC50) values for 21 substances, including 7 plant protection product active substances (chlordane, chlorpyrifos, dieldrin, endosulfan, lindane, malathion, and thiobencarb).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of substances (ammonia, pyrethroid insecticides, organometallics, metals) for which toxicity is different are provided in Matthiessen et al (2010). On the other hand, a recent literature review (Klok et al, 2012) based on 3627 references concludes that there is no systematic difference in sensitivity to pesticides between fresh-and salt-water species. However, at least in the European strategy, seawater AFs are consistently higher than freshwater AFs because fewer marine data are available (Tables 2.1 and 2.2).…”
Section: Environmental Quality Standards and Guidelinesmentioning
confidence: 99%
“…In addition to the lack of representative species, toxicity assessments often depend on the results of toxicity tests performed with temperate species, as data on tropical species are scarce (Kwok et al, 2007). Risk assessments performed for tropical ecosystems should be based on toxicity data from tropical species, since differences in sensitivity might be expected (Daam & Brink, 2010;Klok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%